Development and Sandardization of General Chemistry Practices According to the Demands of Bachelor Pharmaceutical Education Curriculum - Hartika Samgryce Siagian; Ratih Anggraeni (Jurnal Pendidikan dan Pembelajaran Kimia, 2020)
Basic Chemistry is a compulsory subject programmed by the Imelda University Medan Undergraduate Pharmacy Study Program based on the curriculum of the Association of Indonesian Pharmacy Higher Education (APTFI). Basic Chemistry courses equipped with practicum are requirements that must be passed before achieving a bachelor's degree in Pharmacy.Practical activities in the laboratory aim to make students master the techniques or work procedures in the laboratory. One of supporting the implementation of practical activities is the availability of practical guidance that has an active role to guide students doing lab activities. The purpose of practicum activities is to support the mission of MedanImelda University in organizing effective learning.This type of research is development research. Data analysis technique used is descriptive statistical analysis with a questionnaire research instruments validator expert (questionnaire I) and students (questionnaire II). The research stage consisted of 4 stages: (1) developing a framework from developing a practicum guide; (2) develop a practical guide; (3) review and improve practical guide covering expert validation (Lecturer Chemistry) and continued analysis of revision; (4) implement a pilot lab, analyze the response of students continued to draw conclusions.Basic Chemistry Practical Guidebook has been prepared otherwise very decent by two lecturers and 40 students Bachelor Chemical Pharmaceutical DepartmentMedan Imelda University to be used as supporting materials on basic chemistry course with a score of 90% and 88%.